PENGARUH KEPEMILIKAN PERUSAHAAN, CORPORATE GOVERNANCE, DAN EARNINGS MANAGEMENT TERHADAP TIPE AUDITOR DAN AUDIT FEES (Studi Empiris Pada Perusahaan yang Terdaftar di BEI dan IICG Tahun 2011-2013) - Gandhi Prayurgi (Jurnal Akuntansi Indonesia, 2015)
Audit Fee is a dilemmatic problem for an auditor because auditor get a fee from the audited client. On the other side, auditor must be independent in giving their opinion while they also get a fee for services rendered. The purpose of this study is to provide information to companies, auditors, and other information users about the factors that influence the company in selecting the type of auditors and audit fees. The independent variables in this study ar Firm Ownership, Corporate Governance, and Earnings Management with the dependent variablesare the type of auitor and audit fees. Firm ownership in this study was divided into two, the state-owned companies (BUMN)and private companies. Earnings management was measured by discreationary acccruals (DACC) Jones model. Corporate governance in this study was measured by looking at Corporate Governance Perception Index (CGPI). Type of auditors in this study were divided into two, KAP the big four and non-the big four. Audit fees in this studywas measured by natural logarithm of the professional fees. The population of this study is companies listed in the Indonesian Stock Exchange (IDX) and also listed in the Indonesian Institute of Corporate Governance (IICG) in 2011- 2013 with the total sample is 51 company datas for 3 years. The hypotheses in this study were tested using logistic regression and multiple regression. The results of this study indicate that firm ownership does not influence the selection of the type of auditors and audit fees, while corporate governance and earnings management influence the selection of the type of auditors and audit fees.